PENGENALAN POTENSI KELAUTAN DAN PERIKANAN USIA DINI PADA TINGKAT SEKOLAH DASAR MELALUI METODE CERAMAH DAN BERCERITA - NEGARA, I.K. W.; Restu, I.W.; Julyantoro, P.G.S.; Pebriani, D.A.A. (Buletin Udayana Mengabdi; Vol 24 No 3 (2025): Buletin Udayana Mengabdi, 2024)
Galungan, a village located in the Sawan District, plays a crucial role in the management and utilization of its aquatic resources. To increase understanding about the importance of potency maritime and fisheries utilized and maintained sustainability, starting from age early in State Elementary School (SDN), an educational initiative was implemented at SDN 1 and 2 Galungan Village. The observation stage involved coordination and communication with the Principals of SDN 1 and 2. The service implementation stage began at SDN 2 with 15 students and continued to SDN 1 with 28 students. The method used in the two elementary schools was the lecture and storytelling approach, covering topics such as introducing endemic fish on the island of Bali, the functions and benefits of rivers and oceans, protected aquatic animals, the potential for water tourism, and the younger generation's obligation to utilize the potential of marine resources sustainably. After the lecture and storytelling process, which was guided by video and images, the evaluation stage involved a question and answer-session. The results showed that 68% of students at SDN 2 and 73% of students at SDN 1 provided correct answers. The total number of students who dared to ask questions was 25% at SDN 2 and 33% at SDN 1. Where a question-and-answer activity was held, from both schools. The results show that students at SDN 1 and 2 were very enthusiastic about participating in lectures and talking about the potential of marine and fisheries. Keywords: Potential, Marine, Fisheries, Elementary School, Galungan Village